2015
DOI: 10.1016/j.cllc.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Computed Tomography Characteristics for Lung Adenocarcinoma and Their Association With Lung Cancer Survival

Abstract: Background Computed tomographic (CT) characteristics derived from noninvasive images that represent the entire tumor may have diagnostic and prognostic value. The purpose of this study was to assess the association of a standardized set of semiquantitative CT characteristics of lung adenocarcinoma with overall survival. Patients and Methods An initial set of CT descriptors was developed to semiquantitatively assess lung adenocarcinoma in patients (n=117) who underwent resection. Survival analyses were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
1
38
2
Order By: Relevance
“…Our results were consistent with these previous reports. Since it was generally recognized that adenocarcinomas showing GGO on CT usually possess lepidic growth pattern [26], the result is also consistent with the pathologic findings that lepidic growth pattern was more common in lung adenocarcinomas with EGFR mutations than in those with ALK rearrangements. By comparing with those with EGFR mutations, lung adenocarcinomas with ALK rearrangements were reported to be associated with advanced lymph node metastasis [10, 13].…”
Section: Discussionsupporting
confidence: 83%
“…Our results were consistent with these previous reports. Since it was generally recognized that adenocarcinomas showing GGO on CT usually possess lepidic growth pattern [26], the result is also consistent with the pathologic findings that lepidic growth pattern was more common in lung adenocarcinomas with EGFR mutations than in those with ALK rearrangements. By comparing with those with EGFR mutations, lung adenocarcinomas with ALK rearrangements were reported to be associated with advanced lymph node metastasis [10, 13].…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have demonstrated that preoperative computed tomographic (CT) findings are associated with pathological features and postoperative outcomes 8-11 . For example, ground-glass opacity (GGO) was associated with lepidic growth pattern of lung adenocarcinoma, and correlated well with histologic prognostic factors and survival 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is that although automatically extracted features are more reproducible, they are often impeded by variations in image acquisition and/or artifacts. Semantic features following radiologist evaluation show a high degree of agreement (37) but lack the granularity for satisfactory quantitative analysis. Eight of 13 categorical variables (5 from Diehn et al [15] and 3 from VASARI, Gutmnan et al [17]) were replaced with continuous variables.…”
Section: Discussionmentioning
confidence: 99%